Image and imagination - Lewis, C. S.; Hooper, Walter (UK CUP, 2013)
This selection from the writings of C. S. Lewis gathers together forty book reviews, never before reprinted, as well as four major essays which have been unavailable for many decades. A fifth essay, "Image and Imagination", is published for the first time.
Reflections on literature. The idea of an 'English school' -- Our English syllabus -- Image and imagination -- Arundell Esdaile, The sources of English literature -- W.P. Ker, Form and style in poetry : lectures and notes, ed. R.W. Chambers -- Denis de Rougemont, Poetry and society and Claude Chavasse, The bride of Christ -- Oliver Elton (1861-1945) : an obituary -- Howard Rollin Patch, The other world, according to descriptions in medieval literature -- Werner Schwarz, Principles and problems of Biblical translation -- Tragic ends : George Steiner, The death of tragedy -- Eros on the loose : David Loth, The erotic in literature -- The Inklings : Barfield, Tolkien, and Williams. Who gaf me drink? : Owen Barfield, Romanticism comes of age -- G.A.L. Burgeon (=Owen Barfield), This ever diverse pair -- A world for children : J.R.R. Tolkien, The Hobbit, or There and back again -- Professor Tolkien's hobbit : J.R.R. Tolkien, The Hobbit, or There and back again -- The gods return to earth : J.R.R. Tolkien, The fellowship of the ring (being the first part of The lord of the rings) -- The dethronement of power : J.R.R. Tolkien, The two towers (being the second part of The lord of the rings) and The return of the king (being the third part of The lord of the rings) -- Preface from Essays presented to Charles Williams, ed. C.S. Lewis -- A sacred poem : Charles Williams, Taliessin through Logres -- Charles Williams, Taliessin through Logres -- Charles Walter Stansby Williams (1886-1945) : an obituary -- Reflections on Christianity and literature. A lectionary of Christian prose from the second century to the twentieth century, ed. A.C. Bouquet -- The Oxford book of Christian verse, ed. Lord David Cecil -- Dorothy L. Sayers, The mind of the maker -- Selected sermons : A selection from the occasional sermons of Ronald Arbuthnott Knox, ed. Evelyn Waugh -- Foreword to Joy Davidman, Smoke on the mountain : an interpretation of the ten commandments -- Preface to Austin Farrer, A faith of our own -- Classical literature. Odysseus sails again : The odyssey, trans. Robert Fitzgerald -- Ajax and others : John Jones, On Aristotle and Greek tragedy -- Lucretius -- T.R. Henn, Longinus and English criticism -- Helen M. Barrett, Boethius : some aspects of his times and work -- Medieval and Renaissance literature. Ruth Mohl, The three estates in medieval and Renaissance literature -- J.W.H. Atkins, English literary criticism : the medieval phase -- Arthuriana : Arthurian literature in the middle ages : a collaborative study, ed. R.S. Loomis -- Introduction from Selections from Lazamon's Brut, ed. G.L. Brook -- Andreas Capellanus, The art of courtly love, with introduction, translation, and notes by John Jay Parry -- Rhyme and reason : Dorothy L. Sayers, The poetry of search and the poetry of statement -- Alan M.F. Gunn, The mirror of love : a reinterpretation of The romance of the rose -- The English prose Morte -- Leone Ebreo, The philosophy of love (dialoghi d'amore), trans. J. Friedeberg-Seeley and Jean H. Barnes, and intro. Cecil Roth -- E.K. Chambers, Sir Thomas Wyatt and some collected studies -- M. Pauline Parker, The allegory of the Faerie queene -- John Vyvyan, Shakespeare and the rose of love -- Milton and later English literature. Logan Pearsall Smith, Milton and his modern critics -- Douglas Bush, Paradise lost in our time : some comments -- H.W. Garrod, Collins -- Hugh Kingsmill, Matthew Arnold -- Evelyn Waugh, Rossetti : his life and works -- Boswell's bugbear : Sir John Hawkins, The life of Samuel Johnson, ed. Bertram Hylton Davis -- Poetry and exegesis : Harold Bloom, The visionary company : a reading of English romantic poetry -- The sagas and modern life : Morris, Mr. Yeats, and the originals : Dorothy M. Hoare, The works of Morris and of Yeats in relation to early saga literature -- Haggard rides again : Morton Cohen, Rider Haggard : his life and works.